2022
DOI: 10.1101/2022.02.14.480322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic profiling of HIV-1 integration in microglia links viral insertions to TAD organization

Abstract: HIV-1 persists in anatomically distinct cellular and tissue reservoirs as a stably integrated provirus that is a major barrier to HIV-1 cure. Proviral insertions are largely characterized in blood cells, while HIV-1 integration patterns remain unexplored in microglia, the major brain reservoir. Here, we employ genomics approaches to obtain the first HIV-1 integration site (IS) profiling in microglia and perform in-depth analysis of transcriptome, specific histone signatures and chromatin accessibility on diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 111 publications
(214 reference statements)
1
2
0
Order By: Relevance
“…S7C-D). A recent work published the first in vitro microglial IS in the C20 microglial cell line and did not observe the same differences in IS patterns as we observed here compared to T-cells (43). However, based on published RNA-seq data, expression of LEDGF and CPSF6 are significantly higher in C20 cells compared to primary microglia (Fig.…”
Section: Subhead 3: Neuronal and Non-neuronal Integration Site Mappin...supporting
confidence: 74%
See 1 more Smart Citation
“…S7C-D). A recent work published the first in vitro microglial IS in the C20 microglial cell line and did not observe the same differences in IS patterns as we observed here compared to T-cells (43). However, based on published RNA-seq data, expression of LEDGF and CPSF6 are significantly higher in C20 cells compared to primary microglia (Fig.…”
Section: Subhead 3: Neuronal and Non-neuronal Integration Site Mappin...supporting
confidence: 74%
“…Here, we built an integrative dataset from 77 sequencing files, including snRNA-seq, Hi-C, IS-seq, and ChIP-seq, providing a critically needed neurogenomics resource from postmortem brain of infected donors and controls. By providing genome-scale maps for viral integration sites and their disease-associated chromosomal conformation and single nuclei expression states, our resource greatly extends previous, tissue-homogenate based gene expression profiling and integration site analyses in cell culture models ( 43 ).…”
Section: Discussionmentioning
confidence: 95%
“…Recent Hi-C analysis of HIV-1-infected cells revealed that genes recurrently targeted by the virus are proximal to super-enhancer genomic elements that tend to cluster spatially in the nuclei of CD4 + T cells [ 80 ]. Because HIV-1 can invade the central nervous system, productively infecting macrophages and microglia therein, the HIV-1 integration pattern in relation to the 3D genomic architecture of microglia cells was also investigated by Hi-C [ 81 ]. The results further strengthened the notion that HIV-1 integration preferentially occurs at active, open chromatin, including CTCF-bound regions with active histone marks positioned proximal to TAD boundaries.…”
Section: Hiv-1mentioning
confidence: 99%